Investigating the Correlation Between Cognitive Function and Fasting Blood Sugar, Fasting Insulin Level and Insulin Sensitivity in Patients With Multiple Sclerosis - Nasim Rezaeimanesh; Naghme Abbasi Kasbi; Roghayyeh Saeedi; Mohammad Ali Sahraian; Soodeh Razeghi Jahromi; Abdorreza Naser Moghadasi (Endocrinology, Diabetes & Metabolism)
ABSTRACT Introduction There has been a surge in interest in identifying the factors that impact cognitive impairment (CI) in patients with multiple sclerosis (MS). The purpose of our study was to examine the correlation between fasting blood sugar (FBS), fasting insulin level, as well as insulin sensitivity and cognitive function in patients with MS. Material and Methods A total of 85 patients with MS enrolled in this cross‐sectional study. Insulin sensitivity (IS) was determined using the quantitative insulin sensitivity check index (Quicki) formula. Cognitive function was evaluated using the Persian version of the Brief International Cognitive Assessment for MS (BICAMS). Spearman correlation test was employed to examine the correlation between cognition and FBS, insulin and IS. Results The mean ± SD age of the participants was 39.4 ± 10.2 years, and 62 (72.9%) were female. The participants had a FBS level of 87.05 ± 11.73 mg/dL, insulin level of 10.14 ± 7.57 μU/mL and a Quicki index of 0.36 ± 0.05. A higher score on the BVMT‐R and BVMT‐R‐Delayed subtests showed a significant negative correlation with FBS (r: −0.32; p: 0.003 and r: −0.31; p: 0.004, respectively). Conversely, a significant negative correlation (r: −0.24; p: 0.031) was observed between higher fasting insulin levels and the CVLT_II score. IS showed a positive correlation with the CVLT‐II (r: 0.24; p: 0.027) and BVMT_R (r: 0.21; p: 0.054) subtests. Conclusion Our data indicate that elevated fasting glucose, developed fasting insulin levels and reduced insulin sensitivity may serve as potential predictors for CI in patients with MS.